Eurasian economic perspectives : Proceedings of the 20th Eurasia Business and Economics Society Conference, Vol. 2 /: Proceedings of the 20th Eurasia Business and Economics Society Conference, Vol. 2. (2018) - Danis, Hakan; Demir, Ender; Can, Ugur
No abstract available